Зображення західних воїнів на кахлях з розкопок Батурина - Мезенцев, В.І. (Сіверщина в історії України, 2023)
Стаття розглядає відомі натепер рідкісні керамічні полив’яні та теракотові пічні кахлі з фігурами європейських найманців доби гетьманування Івана Мазепи (1687–1709 рр.), знайдені в ході розкопок м. Батурина Чернігівської обл. в 1995–2013 рр. Аналізується вигляд, одяг, прикраси, взуття, озброєння, бойовий обладунок і кінське спорядження зображених воїнів, аргументується їхнє західне походження та спростовуються інші інтерпретації цих сюжетів деякими дослідниками кахлів Батурина. Вказані польські, голландські та інші західноєвропейські мистецькі твори з образами військових XV–XVIII ст. та надруковані зразки, на які могли взорувати батуринські кахлярі. Акцентуються культурні зв’язки столиці Гетьманщини з Європою та впливи барокової графіки на творчість майстрів кахлі у період найвищого розквіту міста за І. Мазепи. Тут описані та опубліковані гіпотетичні комп’ютерно-графічні реконструкції найзначніших цілих антропоморфних кахлів Батурина того часу. This article examines the glazed ceramic and terracotta (unglazed) stove tiles or «kakhli» bearing the relief images of European mercenaries from the reign of Hetman Ivan Mazepa (1687–1709). They were discovered during the 1995–2013 excavations in the town of Baturyn, Chernihiv province, Ukraine, which was the capital of the seventeenth- and eighteenth- century Cossack state, or Hetmanate. The Canada-Ukraine Baturyn Archaeological Project is sponsored by the Canadian Institute of Ukrainian Studies (CIUS) at the University of Alberta and the Ucrainica Research Institute in Toronto, Canada. This project is administered by The Peter Jacyk Centre for Ukrainian Historical Research at the CIUS Toronto Office (https://www.ualberta.ca/canadian-instituteof- ukrainian-studies/centres-and-programs/jacyk-centre/baturyn-project. html). In 2021–2023, CIUS supported it with a grant from the Dr. Bohdan Stefan Zaputovich and Dr. Maria Hrycaiko Zaputovich Endowment Fund. The Ukrainian Studies Fund in New York also supports the Baturyn project with annual subsidies. The most generous individual benefactors of the archaeological and historical investigations of early modern Baturyn are Ms. Love Helen Negrych, Dr. George J. Iwanchyshyn (Toronto), and Michael S. Humnicky (Murfreesboro, TN, USA). The author analyses in details the visages, clothing, ornaments, footwear, weapons, military accoutrements, and horse harness of several infantry officers and cavalrymen portrayed on the tiles and substantiates their Western origins, contesting the other interpretations of these images proposed by the earlier researchers of Baturyn. He believes that its tile-makers («kakhliari») have used as templates some Polish, Dutch, and other European majolica revetment tiles or engravings picturing the militaries from the fifteenth to early eighteenth centuries and presents several examples in the article. These locally manufactured stove tiles with rare depictions of I. Mazepa’s warriors are the most informative, thought-provoking, and representative Baturyn earthenware items from its golden age. They serve as the visual evidence of engaging the European mercenaries in the hetman’s army and allow us to trace the cultural connections between the Cossack capital and the West, including the stimulating influence of baroque graphics on the town’s decorative ceramics. These artefacts provide a valuable new insight into the culture and lifeways, artistic tastes, and Western orientation of the hetman, the Cossack officer class, and wealthy burghers in I. Mazepa’s capital. Thus, our research on the anthropomorphic stove tiles excavated in Baturyn helps to elucidate the theretofore little known culture of the Cossack state capital and its dynamic development within the sphere of European civilization. This article is richly illustrated with the photos of original tiles, drawings of their reliefs, and hypothetical computer graphic reconstructions of two broken tiles with the best human images.